Different pain responses to distinct levels of physical activity in women with patellofemoral pain - Briani, Ronaldo V. [UNESP]; Pazzinatto, Marcella F. [UNESP]; De Oliveira Silva, Danilo [UNESP]; Azevedo, Fábio M. [UNESP] (Elsevier, 2017)
Background Physical activity levels seem to play a role in patellofemoral pain (PFP); however, few studies have been conducted to confirm this hypothesis. Objectives To determine the reported pain levels of women with and without PFP who maintain different levels of physical activity; to determine the capability of these levels to predict pain; and to test the capability of two stair-negotiation protocols, with and without external load, to equalize pain between groups. Method Four groups were divided based on the women's physical activity levels: moderate activity PFP group (28), moderate activity control group (23), intense activity PFP group (22), and intense activity control group (22). All participants were asked to perform 15 repetitions of stair negotiation with and without external load on a seven-step staircase on two separate days. Pain levels were reported using a visual analog scale at five distinct moments: previous month, before stair negotiation, after stair negotiation, before patellofemoral joint (PFJ) loading protocol, and after PFJ loading protocol. Results The intense activity PFP group showed higher levels of pain than the moderate activity PFP group (F(8,158) = 11.714, p = 0.000, η2 = 0.30). The PFJ loading protocol was able to equalize and exacerbate pain in the PFP groups. Conclusion Intense physical activity seems to have a higher association with knee pain than moderate physical activity. A PFJ loading protocol may be an alternative to equalize pain in women with PFP during clinical assessments.
Keywords: Knee pain; Movement; Overuse; Physical activity level; Physical therapy; Rehabilitation